2022
DOI: 10.1002/ejsp.2834
|View full text |Cite
|
Sign up to set email alerts
|

Double standards in the COVID‐19 pandemic: The moderation of perceived threat

Abstract: This research explored whether people hold double standards in a public crisis. We proposed that during the COVID‐19 pandemic, people required others to strictly follow self‐quarantine rules and other preventive behaviors, whereas they themselves would not, demonstrating double standards. Moreover, this effect would be moderated by the perceived threat from the pandemic. Using data collected in the United States and China, three studies ( N = 2,180) tested the hypotheses by measuring (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…Although it was not the focus of the current study, it is also interesting to note that American participants consistently appeared to believe that they did not need to change their behaviour as much as others did, but that this tendency was significantly weaker (in our original study) or not observed at all (in our replication study) among Japanese participants. The pattern of results found among American participants echoes findings that American but not Chinese individuals demonstrated self-serving bias in the context of the pandemic (Dong et al, 2021), and that Americans who were told that the COVID-19 pandemic was abating felt they did not need to take preventative measures as much as others did (Wang et al, 2022). Although the authors of the latter study found similar double standards when asking Chinese participants about adherence to self-quarantine measures, they did not test whether this effect generalised to their perceptions of preventative measures.…”
Section: Adjustmentsupporting
confidence: 59%
“…Although it was not the focus of the current study, it is also interesting to note that American participants consistently appeared to believe that they did not need to change their behaviour as much as others did, but that this tendency was significantly weaker (in our original study) or not observed at all (in our replication study) among Japanese participants. The pattern of results found among American participants echoes findings that American but not Chinese individuals demonstrated self-serving bias in the context of the pandemic (Dong et al, 2021), and that Americans who were told that the COVID-19 pandemic was abating felt they did not need to take preventative measures as much as others did (Wang et al, 2022). Although the authors of the latter study found similar double standards when asking Chinese participants about adherence to self-quarantine measures, they did not test whether this effect generalised to their perceptions of preventative measures.…”
Section: Adjustmentsupporting
confidence: 59%